Electrochemical exfoliation of hierarchical Co3O4 microflowers and their conversion into CoP as high-efficiency hydrogen evolution electrocatalyst. (1st November 2019) - Guo, Manman; Qu, Yaohui; Yuan, Cailei; Chen, Shu
Abstract: The development of simple and green strategies for preparing non-precious metal electrocatalysts is significant for renewable energy storage technologies. We report in this work the fabrication of hierarchical CoP microflowers (HMF CoP) assembled with nanosheets through an electrochemical exfoliation followed by the subsequent optimized phosphorization process. Thanks to hierarchical micro/nanostructure, strong electron interactions between Co and P atoms, large specific surface area (131.31 m 2 g −2 ), and enriched active sites, the as-prepared CoP electrocatalyst exhibits excellent performance with driving a current density 10 mA cm −2 at a low overpotential of 106 mV, a small Tafel slope of 44.5 mV dec −1, and satisfactory durability after 20 h HER testing at 10 mA cm −2 . This work would develop a newfangled strategy to design more non-precious metal nanomaterials as high-efficiency electrocatalysts. Graphical abstract: Efficient hydrogen evolution reaction electrocatalyst based on hierarchical CoP microflowers achieved by electrochemical exfoliation coupling with optimized phosphorization process.Image 1 Highlights: Hierarchical Co3 O4 microflowers were directly exfoliated in a blank alkaline solution. Co3 O4 precursors were phosphorized by optimizing treatment temperature. HMF CoP exhibited a highly active HER property with 10 mA cm −2 at 106 mV overpotential. HER activities were ascribed to large active areas and electron interactions between Co–P.